The Implementation of Guided Inquiry Learning Models on The Concept Mastery, Scientific Attitude, and Science Process Skill (Universitas Negeri Semarang, 2019)
The purpose abstract of this research is (1) analyze the mastery of the concepts in fourth grade in inquiry learning guided; (2) analyze the attitude fourth grade students in inquiry learning guided; (3) analyze the science process skills in fourth grade in inquiry learning’s guided; (4) analyze the different in mastery of concepts, science process skills and scientific attitudes between other students in fourth grade who learn using conventional learning with inquiry learning’s guided. The type of research which has used is quantitative quasi-experimental research method with nonequivalent control group design. The population of the study consist of all fourth-grade students who have ranked includes the Papak Group of Papak Group, Leuwimunding sub-district, Majalengka District. The sample has been selected through a purposive sampling technique, so SDN Rajawangi I was chosen as the control class and SDN Ciparai II as an experimental class. The techniques of data collection using non-test techniques, including interview guidelines, observation guidelines, and documentation. The result of the study show that (1) the application of the guide inquiry approach influences the mastery of concepts are increasing in the N-gain value in the medium category with a score of 0.61; (2) the application of the guide inquiry approach influences the mastery of concepts are increasing in the N-gain value in the medium category with a score of 0.64; (3) the application of the guide inquiry approach influences the science process skills, namely an increase in the N-gain value inquiry in the medium category a score of 0.64; (4) guided inquiry approach can improve mastery of concepts, scientific attitudes and science skill of science. The Sig score obtained is less than 0.05 so, it can be applied that there is mastery of concepts, scientific attitudes and science process skills of students after the guided inquiry approach has been applied with the media in the school environment.